2018
DOI: 10.1111/bcp.13510
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of population pharmacokinetics of valproic acid

Abstract: Keywords nonlinear mixed effect modelling, population pharmacokinetics, systematic review, valproic acid AIMSPopulation pharmacokinetics is an essential tool that helps guide individualized dosing regimens. The aims of this systematic review are to provide knowledge concerning population pharmacokinetics of valproic acid (VPA) and to identify factors influencing VPA pharmacokinetic variability. METHODSPubMed and Embase databases were systematically searched from inception to June, 2017. Relevant articles from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 50 publications
9
71
1
5
Order By: Relevance
“…Several models have been published in the pediatric population, either to describe valproate pharmacokinetics or to predict concentrations. 21 The challenge is to know which model among all published might correspond to our population and could be used in clinical practice. External validation of PPK models uses data collected from a new patient cohort receiving a drug.…”
mentioning
confidence: 99%
“…Several models have been published in the pediatric population, either to describe valproate pharmacokinetics or to predict concentrations. 21 The challenge is to know which model among all published might correspond to our population and could be used in clinical practice. External validation of PPK models uses data collected from a new patient cohort receiving a drug.…”
mentioning
confidence: 99%
“…Most of them had a one-compartment model structure developed based on TDM data. A systematic review of population pharmacokinetics of valproic acid reported that only 65% of the developed models were evaluated for their performance and appropriateness (eg, bootstrap analysis, goodness of fit plots, predictive check) 22. Additionally, the United States Food and Drug Administration suggested that external evaluation of a population pharmacokinetic model is the most stringent method for assessment of a developed model 1.…”
Section: Discussionmentioning
confidence: 99%
“…Valproic acid (VPA) is effective for the prevention of various seizures, and it is widely used in the developing world as it is inexpensive. 3 The adverse effects of VPA include vomiting, nausea, and sleepiness. More seriously, the risk of liver damage induced by VPA is presented time-and dose-dependently.…”
Section: Funding Informationmentioning
confidence: 99%
“…The principal therapy of epilepsy is daily antiepileptic drugs for the entire life. Valproic acid (VPA) is effective for the prevention of various seizures, and it is widely used in the developing world as it is inexpensive . The adverse effects of VPA include vomiting, nausea, and sleepiness.…”
Section: Introductionmentioning
confidence: 99%